1998
DOI: 10.1029/98jb00200
|View full text |Cite
|
Sign up to set email alerts
|

Frictional heating on faults: Stable sliding versus stick slip

Abstract: Abstract. Laboratory experiments were performed where heat generation was measured during both stable sliding and stick-slip friction. For a given average slip velocity, stick-slip sliding produces heat at a considerably lower rate than stable sliding without appealing to high pore pressure or lubrication. These experiments show that faults can be apparently both "strong" when slip initiates and "weak" during rapid sliding, suggesting that different mechanisms operate under the two sliding conditions. If these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 25 publications
4
23
0
Order By: Relevance
“…Our study shows that temperature increases systematically as a function of both normal stress and sliding velocity, as observed previously in granular layers at lower normal stress conditions (LOCKNER and OKUBO, 1983) and on bare granite surfaces (BLANPIED et al, 1998;BROWN, 1998). We verify that the heat production equation holds for all tests.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…Our study shows that temperature increases systematically as a function of both normal stress and sliding velocity, as observed previously in granular layers at lower normal stress conditions (LOCKNER and OKUBO, 1983) and on bare granite surfaces (BLANPIED et al, 1998;BROWN, 1998). We verify that the heat production equation holds for all tests.…”
Section: Discussionsupporting
confidence: 68%
“…This explains why the rapid increase in temperature associated with the faster (shaded) velocity reaches the sensor during the subsequent low velocity (unshaded) part. The rate of temperature rise (the slope of the perturbations) systematically increases with normal stress, consistent with results from bare surface experiments (BROWN, 1998). At any specific shear displacement, the temperature rise observed is systematically larger at higher normal stress.…”
Section: Temperature Measurements: Velocity Stepping Testssupporting
confidence: 76%
See 2 more Smart Citations
“…In this article we report the results of a series of laboratory experiments that looked in greater detail than did previous studies at the relationship between normal stresses and stickslip frictional sliding. These experiments were based on previous studies that had indicated that fault-normal stress reduction and reduced heat generation accompanied stick slip on a pre-cut fault in a polycarbonate sample [Brown et al, 1991;Brown, 1994a;1998] …”
mentioning
confidence: 99%